Formal Analysis of Segregation of Duties (SoD) in Accounting: A Computational Approach. - Kim, Rosemary; Gangolly, Jagdish; Ravi, S. S.; Rosenkrantz, Daniel J. (Abacus, 2020)
This study examines a computational framework for segregation of duties (SoD) in the design as well as implementation of accounting systems. The framework consists of a model of workflows in accounting systems based on workflow graphs, a partial order model of roles performed by the actors in the accounting system, and a specification of SoD rules. We develop a set of algorithms for four SoD rules that can be used in the enforcement of SoD. For the SoD rule that precludes task type conflicts, our results show that while compliance verification can be carried out efficiently, finding an SoD compliant assignment of tasks is computationally intractable. For those situations, we present an integer linear programming (ILP) formulation for finding compliant assignments using public domain ILP solvers. For the remaining three SoD rules, we demonstrate efficient ways of testing compliance for a given assignment as well as finding compliant assignments.